Avaliação da associação entre uso da cabergolina e a presença de valvopatia em pacientes portadores de acromegalia - Farias, Ludmilla Aline Guimarães Moreira (2016)
BACKGROUND:Acromegaly is a disorderassociated with increased mortality, mainly due to cardiovascular disease, caused by chronic excessive GH secretion. Regular echocardiographic assessment is recommended to evaluate cardiac morphological disorders, including valvopathy. One of the therapeutic options is the use of cabergoline (CAB). This medication has been associated with lesions to the cardiac valve apparatus when used in patients with Parkinson´s disease or Prolactinoma, but data on acromegalic patients are scant.OBJECTIVE:Compare the prevalence of valvopathy among patients with acromegaly who have used cabergoline and those who have not.METHODS:The present study is cross-sectional and observational analytical.Echocardiography was performed for two cardiologists blinded to treatment, and laboratory tests weremade and patients’ medical records were reviewed for clinical data collection. Patients were divided into two groups according to usage (CAB group) or not (control group)of cabergoline. SPSS v17 was used for statistical analysis. RESULTS:Fifty two patientswere evaluated, 35 in the CAB group and 17 in the control group. The distribution of sex and age, and the prevalence of hypertension, diabetes and obesity were similar in both groups. In the CAB group, the period of drug administration was 36 ± 27 months, and cumulative dose was 262 ± 178mg. The prevalence of regurgitation in any valve was, for CAB group and Control group respectively 42,9 vs 23,5% (P=0,175, both observers). The prevalence of remodeling in any valve was37,1 vs 23,5% (P=0,326, observer 1) and 42,9 vs 23,5% (P=0,175, observer 2). CONCLUSION:In our study, the use of cabergoline was not associatedwith valvulopathy in patients with acromegaly. Our data do not support modification of current guidelines of echocardiographic evaluation in these patients according to the use of cabergoline.